(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The given article is devoted to identifying the cognitive dissonance through linguistics potential of comments on the basis of the English media discourse. The review of the authors who researched the problem is given, as well as their works. Currently, the topical issue is the study of media discourse together with the discourse of comments, which gives a complete picture of how a particular media discourse is perceived by people. Notions of “comments”, “cognitive dissonance”, “discourse”, “media discourse” are considered. Recipients of information may experience a state of cognitive dissonance, in a situation where new information does not correspond to the ideas previously embedded in their minds. Users express this dissonance in social networks with the help of comments. Also, the article provides an example of media discourse and comments to it. Methods applied in the process of research are include the following: discourse analysis, content analysis, and functional-stylistic analysis.